(untitled) (Revista Iberoamericana de Bioética, 2025)
Surrogacy raises ethical challenges concerning autonomy, social justice, and reproductive rights. This article takes a bioethical perspective to examine how feminism and utilitarianism can provide a foundation for fair regulatory frameworks governing this practice. Through a systematic review of academic literature (2015-2024) and a comparative analysis of international regulations (Canada, United Kingdom, Ukraine, United States), it identifies tensions between the protection of surrogate mothers and reproductive rights. The findings highlight that: (1) liberal feminism supports surrogacy under informed consent, whereas radical feminism criticizes it as a form of exploitation; (2) utilitarianism justifies the practice if it maximizes collective well-being, although it overlooks structural inequalities. The article concludes that a global regulatory framework should balance autonomy, protection against exploitation, and the rights of the child, while prioritizing human dignity.